2020
DOI: 10.3171/2020.3.spine20134
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of inpatient admission in the setting of anterior lumbar interbody fusion: a Minimally Invasive Spine Study Group (MISSG) investigation

Abstract: OBJECTIVEWhile the anterior lumbar interbody fusion (ALIF) procedure may be amenable to ambulatory surgery, it has been hypothesized that limitations such as the risk of postoperative ileus and vascular complications have hindered transition of this procedure to the outpatient setting. Identification of independent risk factors predisposing patients to inpatient stays of ≥ 24 hours after ALIF may facilitate better postsurgical outcomes, target modifiable risk factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…In addition, they found that two level procedures were less likely to be conducted in an outpatient setting 24. Moreover, Parrish et al 22 described a series of outpatient ALIF procedures and found that those patients were less likely to have a diagnosis of herniated nucleus pulposus, less likely to have degenerative disk disease along with foraminal stenosis, less likely to have pathology at L4-5, and less likely to have retrolisthesis or lateral listhesis. Kamalapathy et al 25 reported in ALIF patients, older patients, patients with BMI more than 30, and those with a higher comorbidity burden were more likely to undergo inpatient procedures.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they found that two level procedures were less likely to be conducted in an outpatient setting 24. Moreover, Parrish et al 22 described a series of outpatient ALIF procedures and found that those patients were less likely to have a diagnosis of herniated nucleus pulposus, less likely to have degenerative disk disease along with foraminal stenosis, less likely to have pathology at L4-5, and less likely to have retrolisthesis or lateral listhesis. Kamalapathy et al 25 reported in ALIF patients, older patients, patients with BMI more than 30, and those with a higher comorbidity burden were more likely to undergo inpatient procedures.…”
Section: Resultsmentioning
confidence: 99%
“…28 Rothenfluh et al 29 also considered the role of age as a risk factor and observed a higher complication rate (29%) among patients above 60 years compared with a younger cohort, although this trend did not reach statistical significance. Parrish et al 13 investigated the role of advanced age in placing patients at increased likelihood for prolonged postoperative length of stay; however, they too did not find this characteristic to be a significant contributor. Nevertheless, the current study deemed age as a clinically significant operative risk factor and was therefore included among modifiers of ALIF risk.…”
Section: Modifiers Of Riskmentioning
confidence: 99%
“…Operations involving multiple levels of the spine and in particular the L4-L5 level have been implicated as higher risks for complications and increased blood loss. 7,[11][12][13] A range of other factors have been reported to increase risk including a history of prior abdominal surgery, 14 increased body mass index (BMI), 7 male sex, 7 and segmental instability. 11,13 With a large variability in potential risk factors for poorer operative outcomes, the aim of the current study is to provide an objective scoring system to determine the preoperative risk an ALIF presents for a given individual.…”
mentioning
confidence: 99%
“…10,11,15,16 While several studies have analyzed outpatient spine procedures, only a few small institutional cohort studies have specifically evaluated postoperative complications of ALIF in the outpatient setting. 17 There is still concern for intraoperative vascular injury during ALIF that ranges from 1.9% to 24%. 8,18,19 Therefore, the aim of this investigation was to utilize a national database to (1) evaluate differences in postoperative outcomes and cost associated with outpatient ALIF compared with inpatient ALIF, and (2) identify independent factors contributing to complications after outpatient ALIF.…”
mentioning
confidence: 99%
“…While several studies have analyzed outpatient spine procedures, only a few small institutional cohort studies have specifically evaluated postoperative complications of ALIF in the outpatient setting 17. There is still concern for intraoperative vascular injury during ALIF that ranges from 1.9% to 24% 8,18,19.…”
mentioning
confidence: 99%